2019
DOI: 10.1002/lno.11370
|View full text |Cite
|
Sign up to set email alerts
|

Think global, act local: The small‐scale environment mainly influences microbial community development and function in lake sediment

Abstract: The early stages of community development influence longer-term establishment of species, traits, and ultimately ecosystem function. How this process varies with small-and large-scale abiotic and biotic conditions is poorly studied in microbes. Here, we tested how different spatial scales influenced the rate at which taxonomic and functional composition of microbial communities changed over time in lake sediments, and whether these changes occurred synchronously across different environments given the same ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 96 publications
4
18
0
Order By: Relevance
“…These findings are consistent with observational evidence that the abundance rather than presence of bacterial taxa is limited by resource availability in sediments (Louca et al 2018;Orland et al 2019). Our study, therefore, supports the necessity to sample multiple sites and consider sediments differently from the water column when bacterial processes are upscaled to entire estuary basins (Orland et al 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with observational evidence that the abundance rather than presence of bacterial taxa is limited by resource availability in sediments (Louca et al 2018;Orland et al 2019). Our study, therefore, supports the necessity to sample multiple sites and consider sediments differently from the water column when bacterial processes are upscaled to entire estuary basins (Orland et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Neither bottom water temperature or dissolved NO x concentrations showed significant correlations with the sediment microbiomes, suggesting that bacterial groups are more tightly controlled by local sediment abiotic and biotic parameters rather than large fluctuations in the overlying bottom water. The disconnect between the bottom water and the sediment has important ramifications, because it has been suggested that dynamic water column changes, including nutrient bursts, may have little effect on the compositional dynamics of sediment microbes (Orland et al 2020). These findings suggest that rather than an indication of current state, perhaps our data give some indication of trajectory or temporal stability.…”
Section: Discussionmentioning
confidence: 73%
“…Lake sediments are a useful system for studying relationships between microbial community composition and ecosystem function because sediment microbial communities mediate carbon diagenesis and fate and are an important component in carbon cycling (Fitch et al, 2018; Jones & Simon, 1981; Orland et al, 2020; Schwarz et al, 2008). Additionally, differences in the composition of sediment microbial communities have been linked to variation in rates of carbon biogeochemistry (rates of CO 2 and CH 4 production) across the landscape (Bertolet et al, 2019; Matheus Carnevali et al, 2018; Weise et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…pH is widely recognized as an important environmental determinant of sediment microbial community composition (Orland et al, 2020; Tripathi et al, 2018; Xiong et al, 2012), especially of the composition and activity of the methanogen community. Lake sediment methanogen communities are consistently differentiated by pH (Bertolet et al, 2019; Phelps & Zeikus, 1984; Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Within the aquatic microbial community organisms tightly linked to the sediment of waterbodies, or the sediment microbial community, are of special interest (Orland et al, 2020). This is a complex assemblage occupying different layers of sediment with distinct physical and chemical conditions (Spring et al, 2000).…”
Section: Introductionmentioning
confidence: 99%